The landscape design process - Clokey, Jora; Stoltz, Ron; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
Examine basic landscape design steps including the design program, site analysis, concept development, master planning and design, as well as project installation
Title from title screen
DVD format
Keywords: Landscape design; Landscape architecture